2017
DOI: 10.1016/j.ijthermalsci.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-domain optical tomographic image reconstruction algorithm with the simplified spherical harmonics (SP3) light propagation model

Abstract: We introduce here the finite volume formulation of the frequency-domain simplified spherical harmonics model with n-th order absorption coefficients (FD-SPN) that approximates the frequency-domain equation of radiative transfer (FD-ERT). We then present the FD-SPN based reconstruction algorithm that recovers absorption and scattering coefficients in biological tissue. The FD-SPN model with 3rd order absorption coefficient (i.e., FD-SP3) is used as a forward model to solve the inverse problem. The FD-SP3 is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast, the reconstruction time with the ERT model exceeded 100 min on the same computing platform [33]. Additionally, reconstructions with the ERT always required over 6 GB of RAM, while the DE and SP 3 models always required less than 200 MB of RAM [37,38].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, the reconstruction time with the ERT model exceeded 100 min on the same computing platform [33]. Additionally, reconstructions with the ERT always required over 6 GB of RAM, while the DE and SP 3 models always required less than 200 MB of RAM [37,38].…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that the SP 3 model is reliable for use in much of both transport and diffusion regimes, with higher-than-DE accuracy and similar-to-DE speed [38]. In 2017, we reported that the FD-SP 3 model was able to accurately capture the differences in optical properties due to the onset of RA using the forward and inverse simulations of RA-affected and healthy subjects [37].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, this expression can only be applied to simple scene geometries, such as a single homogeneous slab, and assumes that the scene is highly scattering [8]. As a consequence the approximation is not appropriate in many situations such as (a) near surface, where we are not yet in the diffuse regime, (b) inhomogeneous tissue or (c) layered tissue that contain low-scattering regions (such as skull, cerebrospinal fluid and brain) [29]. Monte Carlo simulations of the forward model.…”
Section: Computation Of the Sensitivity Matrixmentioning
confidence: 99%